Pengaruh Diskon Dan Cashback Terhadap Frekuensi Pembelian Pada Aplikasi Shopeefood Di Wilayah Kabupaten Jember - Naylul Nabila; Roro Aditya Novi Wardhani Wardhani; Nike Norma Epriliyana (University of Muhammadiyah Malang, 2025)
This study aims to examine the effect of discount and cashback programs on the frequency of purchases on the Shopeefood application. The background of this research is the rapid development of e-commerce in Indonesia, where Shopee remains the leader with the highest number of monthly visits by 2023. Shopeefood, as one of the main services on this platform, uses various promotional strategies to attract more users, one of which is the discount and cashback program. This study highlights that Shopeefood's strategies, especially the use of discounts and cashback, contribute to an increase in transactions. Discounts provide an immediate price cut that appeals to consumers while cashback offers a financial incentive in the form of a refund that encourages consumers to shop more frequently in the future. However, there are some complaints from consumers regarding the relatively long period of receiving cashback and the less transparent application process, which may affect their level of satisfaction. Through a quantitative approach with multiple linear regression analysis and hypothesis testing, this study found that discount and cashback programs have a significant influence on the frequency of purchases at Shopeefood. The results of this study are expected to provide valuable insights for companies to develop more effective marketing strategies, not only in increasing purchase frequency, but also in building consumer loyalty amid increasingly fierce competition in the food delivery service industry.